KINERJA APARAT PEMERINTAH DALAM PELAYANAN PUBLIK DI KANTOR DESA ENTIKONG KECAMATAN ENTIKONG KABUPATEN SANGGAU - Ningsih E.21109064, Febrianti (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The title of this research is the Government Apparatus Performance in Public Service in the Office of  Rural Entikong the District Entikong regency Sanggau. The existence of public service issues are still given the time constraints in the form of speed, attitude late in administrative services and often not present some apparatus during business hours. This study aims to explain the performance of government officials in the ministry of family cards and identity cards in the village Entikong. Still many villagers who complained about the performance of the services provided at the village office, and service delivery processes in population administration continued and increased in order to achieve optimal service performance. This study used a descriptive research model with data processing techniques of qualitative analysis. In this study, the performance of public service includes 3 things: responsiveness, responsibility, and accountability. The results of the data analysis showed that aspiration which is collected less quickly addressed, the service provided village officials are still deemed to be incompatible with the principles of correct administration, and still felt less consistent and less responding to what the community's problems and not in accordance with the applicable regulations. The conclusion of this study is the readiness of the apparatus that is still lacking in the procurement documents and procedures will be adhered to when public officials do not have an informal relationship with the authorities.Key words: Performance, Public Service, Responsiveness, Responsibility, and Accountability